Varicocele: An Endocrinological Perspective - Bellastella, Giuseppe; Carotenuto, Raffaela; Caiazzo, Francesco; Longo, Miriam; Cirillo, Paolo; Scappaticcio, Lorenzo; Carbone, Carla; Arcaniolo, Davide; Maiorino, Maria Ida; Esposito, Katherine (Frontiers in Reproductive Health, 2022)
Varicocele affects 15% of male population but it is more frequently identified in patients searching medical care for infertility. The impact of varicocele on semen production and fertility is known, but the relationship between clinical varicocele and impaired hormonal production is not clear. In published literature there are some studies regarding hormonal alterations in patients with varicocele but no review in which all the hormonal findings are explained. The aim of this review is to evaluate, by most common search engine, what is known about hormonal alterations in varicocele-bearing patients, to verify if a cause-effect relationship is documented and to give a useful contribution to in clinical management of this kind of patients. We found contradictory results about hormonal status from literature. Some studies confirmed a decrease of testosterone levels and higher FSH and LH levels that normalize after varicocelectomy, others found lower than normal levels of dihydrotestosterone due to decreased activity of epididymal 5-α-reductase. Lower circulating Anti-Müllerian Hormone levels, accompanied by a decreased Inhibin-B level, were reported as indicators of the decreased Sertoli cells function in varicocele-bearing adult patients. The finding of higher basal 17-OH-progesterone concentrations in patients with varicocele was explained by some authors with a testicular C-17,20-lyase deficiency. There is no doubt that varicocele could led to hormonal alterations. This review proposes that the impaired free sexual steroid levels are the result of a slight, deep-rooted defect in the testes of a certain amount of men with varicocele but further multicentre, randomized controlled studies remain mandatory to better clarify the hormonal features of patients with varicocele and to assess the utility of hormonal evaluation for establishing the duration of varicocele and for better identifying patients who need surgical correction.